Hadis tentang Politik - Raodatul Jannah (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this study is to discuss the explanation of hadith about politics. This research method is a qualitative type through literature study by applying content analysis. The discussion of this research includes how the general view of political hadith, how the basic concept of leadership in the perspective of hadith, and how the law of women's political leadership. This study concludes that political rights are not only addressed to men, according to some scholars, women have political rights. However, there are some other scholars who forbid women to participate in politics. Whoever the person, whether male or female, if they have entered the political realm, must pay attention to ethics as befits a good politician, who follows what has been taught by the Prophet Muhammad. This research is expected to have benefits for enriching the treasures of Islamic knowledge.